Seasonal variation in Blueberry scorch virus concentration in highbush blueberry and implications for disease monitoring and management - Raworth, David A.; Mathur, Sneh (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2009)
Seasonal variation in relative Blueberry scorch virus (BlScV) concentration was determined for three infected highbush blueberry, Vaccinium corymbosum, cultivars in a commercial field in southwestern British Columbia, Canada. Relative virus concentration per g of infected blueberry flower clusters and leaf terminal tissue varied during the season with significant cultivar-by-time interactions. Flower clusters had the highest BlScV concentration per g of tissue and could be collected in early May for disease surveys. Timing of leaf sample collection for BlScV surveys, transmission studies and virus purification should be based on studies of temporal variation in BlScV concentration for the principal cultivars in a production area.